Photogrammetric Monitoring of an Artificially Generated Shallow Landslide. (26th April 2013) - Akca, Devrim
Abstract An artificial rainfall event was applied to a forested slope in Ruedlingen, northern Switzerland. The experiment triggered a landslide which resulted in mobilising about 130 m3 of debris. The event was monitored by a photogrammetric network of four cameras, operating at 5 to 8 frames per second, in order to quantify spatial and temporal changes by tracking tennis balls pegged into the ground. Image measurements were performed using automated image matching methods, implemented through a software package developed in‐house. Three‐dimensional coordinates of the target points were estimated by running a customised type of bundle adjustment, achieving a positioning precision of ± 1·8 cm.